Robust dynamic state feedback for underactuated systems with linearly parameterized disturbances - Franco,E; Rodriguez,y Baena F; Astolfi,A (International Journal of Robust and Nonlinear Control, 2020)
This article investigates the control problem for underactuated portcontrolled Hamiltonian systems with multiple linearly parameterized additive disturbances including matched, unmatched, constant, and statedependent components. The notion of algebraic solution of the matching equations is employed to design an extension of the interconnection and damping assignment passivitybased control methodology that does not rely on the solution of partial differential equations. The result is a dynamic statefeedback that includes a disturbance compensation term, where the unknown parameters are estimated adaptively. A simplified implementation of the proposed approach for underactuated mechanical systems is detailed. The effectiveness of the controller is demonstrated with numerical simulations for the magneticlevitatedball system and for the ballonbeam system.